Construction and expression of hybrid plasmids containing Escherichia coli K-12 uxu genes. - Ritzenthaler, P (1980)
The three genes of the Escherichia coli K-12 uxu region (uxu operon and regulatory gene) were isolated on a ColE1-uxu hybrid plasmid from the bank of Clarke and Carbon, and a restriction map of this region was established. In vitro recombination techniques were used to subclone the uxu restriction fragments into the plasmid vector pBR322 or pBR325. The various chimeric plasmids obtained were analyzed by restriction mapping and characterized genetically by introducing them in uxu mutant or wild-type strains. Differential rates of synthesis of the enzymes coded for by the uxu region were measured in the plasmid-containing strains; amplification of the products of the cloned genes was up to 40-fold the level found in haploid strains. The enzymes coded for by uxuA and uxuB were synthesized in vitro in a coupled transcription-translation system, confirming the results of the cloning experiments. The restriction analysis also suggests that the transcriptional direction of the uxu operon is from uxuA to uxuB and that the order of the loci in this region is: uxuR (regulatory gene), uxuB, uxuA, uxuAp (promoter), uxuAo (operator).